Pengaruh Harga, Kualitas Produk, Dan Electronic Word Of Mouth Terhadap Minat Beli Ulang Konsumen Pada Produk Kopi Keliling Merek Sejuta Jiwa Di Desa Wanajaya, Kabupaten Bekasi - Hamdi, Ferdiyan; Untari, Dhian Tyas; Rohaeni, Heni (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the influence of Price, Product Quality, and Electronic Word of Mouth (e-WOM) on Repurchase Intention among consumers of the mobile coffee brand